PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA DI KABUPATEN MUNA - Saltifa, Wa Ode Vira; Palilati, Alida; Isalman, Isalman; Awasinombu, Aidin Hudani; Putera, Asrip (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to determine (1) whether product quality affects the decision to purchase a motorcycle. (2) To find out whether the price affects the decision to buy a motorcycle. (3) To find out whether Brand Image influences the decision to buy a motorcycle. (4) To find out whether Product Quality, Price and Brand Image affect the decision to buy a motorcycle. The results showed that (1) Product Quality, Price and Brand Image simultaneously (together) have a significant effect on purchasing decisions. This shows that increasing the two variables will have an impact on increasing purchasing decisions for Honda motorcycles in Muna Regency, (2) Product quality partially has a significant effect on purchasing decisions. This shows that increasing the product quality variable will have an impact on increasing purchasing decisions for Honda motorbikes in Muna Regency. (3) Price partially has a significant positive effect on purchasing decisions. This shows that increasing the price variable will have an impact on increasing purchasing decisions for Honda motorcycles in Muna Regency, (4) Brand image partially has a significant effect on purchasing decisions. This shows that increasing the Brand Image variable will have an impact on increasing consumer purchasing decisions for Honda Motorcycles in Muna Regency.